2016
DOI: 10.1073/pnas.1606519113
|View full text |Cite
|
Sign up to set email alerts
|

Chloroplast-mediated regulation of CO 2 -concentrating mechanism by Ca 2+ -binding protein CAS in the green alga Chlamydomonas reinhardtii

Abstract: Aquatic photosynthetic organisms, including the green alga Chlamydomonas reinhardtii, induce a CO2-concentrating mechanism (CCM) to maintain photosynthetic activity in CO2-limiting conditions by sensing environmental CO2 and light availability. Previously, a novel high-CO2–requiring mutant, H82, defective in the induction of the CCM, was isolated. A homolog of calcium (Ca2+)-binding protein CAS, originally found in Arabidopsis thaliana, was disrupted in H82 cells. Although Arabidopsis CAS is reported to be ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
71
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(74 citation statements)
references
References 45 publications
3
71
0
Order By: Relevance
“…Under very low CO 2 conditions, the LCIB/LCIC complex, whose role is still uncertain (Jin et al, 2016), is known to form puncta around the pyrenoid periphery (Yamano et al, 2010). Recently, a Ca 2+ -binding protein, CAS, has been shown to specifically localize to the pyrenoid tubules at low CO 2 (Wang et al, 2016). Here, we identify seven additional pyrenoid-localized components and three previously un-described sub-pyrenoid localization patterns (Figure 4B–D).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Under very low CO 2 conditions, the LCIB/LCIC complex, whose role is still uncertain (Jin et al, 2016), is known to form puncta around the pyrenoid periphery (Yamano et al, 2010). Recently, a Ca 2+ -binding protein, CAS, has been shown to specifically localize to the pyrenoid tubules at low CO 2 (Wang et al, 2016). Here, we identify seven additional pyrenoid-localized components and three previously un-described sub-pyrenoid localization patterns (Figure 4B–D).…”
Section: Resultsmentioning
confidence: 99%
“…Recent work has shown that Ca 2+ signalling is key for proper regulation of the CCM, with the Ca 2+ -binding protein CAS1 transcriptionally regulating HLA3 and other components (Wang et al, 2016). One HCIP of HLA3 is an EF-hand-containing Ca 2+ /calmodulin-dependent protein kinase (Cre13.g571700), which could potentially regulate HLA3 post-translationally.…”
Section: Resultsmentioning
confidence: 99%
“…In Arabidopsis, CAS crucially functions in the generation of cytosolic and stromal Ca 2+ transients as well as in the modulation of MAPK signaling (Guo et al, 2016). Moreover, it is involved in photo-acclimation in Chlamydomonas reinhardtii by contributing to the control of expression of LHCSR3 and to the expression of proteins related to the carbon-concentrating mechanism (Petroutsos et al, 2011;Wang et al, 2016b). Also the activity of the cyclic electron flow (CEF) is modulated via CAS and the availability of Ca 2+ in C. reinhardtii and in Arabidopsis (Terashima et al, 2012;Takahashi et al, 2013;Strand et al, 2015).…”
Section: Ca 2+ Signaling In Mitochondria and Chloroplastsmentioning
confidence: 99%
“…Actually, PsbP is considered to be evolutionarily recruited as a replacement of Cc 550 in the photosynthetic green lineage, playing a similar role stabilizing the binding of Ca 2+ , and thus increasing PSII affinity for this ion (Frazão et al , Roncel et al ). Moreover, a Ca 2+ ‐binding protein (CAS) has been also recently shown to specifically localize into the intrapyrenoid thylakoids of C. reinhardtii (Wang et al ). Thus, the presence of Cc 550 in the pyrenoid of P. tricornutum could be related to its role as a calcium‐binding stabilizing protein.…”
Section: Resultsmentioning
confidence: 99%